2020
DOI: 10.4054/demres.2020.42.9
|View full text |Cite
|
Sign up to set email alerts
|

Remain, leave, or return? Mothers’ location continuity after separation in Belgium

Abstract: BACKGROUND Partnership dissolution can mark an extended period of residential instability for mothers and their children. Location continuity, i.e., the ability to stay in or return to the same neighbourhood after separation, is essential to reduce the negative consequences of separation. OBJECTIVE We focus on mothers' post-separation location continuity in the three years following separation and study the role of socioeconomic resources and local ties (to a home, neighbourhood, and region) in remaining in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Parents who experienced separating from the other parent of their children and repartnering during the same calendar year seem to be a specific group that is particularly likely to migrate during this year (men: OR = 16.80; women: OR = 22.67). This finding is consistent with that of Schnor and Mikolai ( 2020 ), who showed that repartnering at separation lowers mothers’ likelihood of staying in the prior joint home and increases their likelihood of moving to another municipality or province. It seems likely that many of these parents initiated the separation because of their new romantic involvement and consequently moved out.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Parents who experienced separating from the other parent of their children and repartnering during the same calendar year seem to be a specific group that is particularly likely to migrate during this year (men: OR = 16.80; women: OR = 22.67). This finding is consistent with that of Schnor and Mikolai ( 2020 ), who showed that repartnering at separation lowers mothers’ likelihood of staying in the prior joint home and increases their likelihood of moving to another municipality or province. It seems likely that many of these parents initiated the separation because of their new romantic involvement and consequently moved out.…”
Section: Resultssupporting
confidence: 92%
“…For Sweden, Brandén and Haandrikman ( 2018 ) showed that the average distance of moving at the start of co-residence is 50 km for men and 59 km for women. Repartnering upon or after separation was found to increase mothers’ likelihood of moving to another municipality or province within Belgium (Schnor & Mikolai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They provide the first analyses of the residential and housing consequences of divorce for an Eastern European (Hungary by Murinkó 2019) as well as a Southern European country (Italy by Fiori 2019). The papers focus on the role of repartnering (Jalovaara and Kulu 2019;Schnor and Mikolai 2020), child custody arrangements (Ferrari, Bonnet, and Solaz 2019), the parental home (Murinkó 2019), location continuity (Schnor and Mikolai 2020), country context , and gender (all studies) for postseparation residential outcomes and trajectories .…”
Section: Discussion and Opportunities For Future Researchmentioning
confidence: 99%
“…In the following we draw on recent work by Schnor and Mikolai (2020), who provide a detailed description of Belgium's housing market. Homeownership, or living in owneroccupied accommodation, is normative in Belgium (Fikse and Aalbers 2020), as shown by its high prevalence of homeownership (69% in 2001) compared to other European countries, and its housing structure marked by short supply of affordable rental housing (OECD 2015(OECD , 2017.…”
Section: Housing Tenurementioning
confidence: 99%
“…A much higher proportion of tenants (34%) than owners (2.4%) spend 40% or more of their income on housing. The financial means of tenants have weakened over time, which makes renting financially difficult and undesirable as a tenure status (Halleux and Strée 2012;Hiscock et al 2001;OECD 2015: 85;Schnor and Mikolai 2020). Belgium's 2001 census data shows that single women and single mothers are at risk, with very little access to homeownership and good-quality housing (Vanneste et al 2007).…”
Section: Housing Tenurementioning
confidence: 99%